(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Effectiveness on The Use of E-Commerce of Cactus and Succulent Businesses in Bali. Marketing through e-commerce has a great opportunity to increase sales. Cactus and succulent businesses in Bali have started implementing e-commerce. However, the number of cactus and succulent businesses actors in Bali using e-commerce is not much compared to non-e-commerce. The purpose of this study is to find out the mechanism of using e-commerce, to analyze effectiveness of using e-commerce, and to identify and analyze constraints of using e-commerce in cactus and succulent businesses in Bali. This study is a qualitative study that is quantified using a score approach. The informants of this study are the businesses actors of Four Ribs Garden, Astro Hijau, and Taru Tresna. Data was collected through interviews with questionnaires and documentation. The results of this study so that the mechanism of using e-commerce in cactus and succulent businesses in Bali including order notifications, order details, order delivery arrangements, and the process of packaging and shipping orders. The use of e-commerce in cactus and succulent businesses in Bali is effective to increase sales based on sales turnover, number of customers, capital expenditures, and the application of discounts up to 100%. The constraints of using e-commerce in cactus and succulent businesses in Bali consist of technical and non-technical constraints. Technical constraints come from features and systems in e-commerce applications. Non-technical constraints are caused by expeditions and the lack of cactus and succulent businesses in Bali in understanding the features and systems of e-commerce. It is suggested to maximize the use of e-commerce features especially in sales education and promotion features to increase the effectiveness of using e-commerce in sales.